2007
DOI: 10.1103/physrevb.75.035116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Vignale-Kohn current functional in the calculation of the optical spectra of semiconductors

Abstract: Analysis of the Vignale-Kohn current functional in the calculation of the optical spectra of semiconductors Berger, J. A.; de Boeij, P. L.; van Leeuwen, R. Copyright Other than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), unless the work is under an open content license (like Creative Commons).Take-down policy If you believe that this document breaches copyright please contact us provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 60 publications
(75 reference statements)
0
23
0
Order By: Relevance
“…Moreover, it allows us to compare our results to static magnetizabilities reported in the literature that were obtained within the LDA. We note that exchangecorrelation vector potentials can be used within this formalism but the known functionals [24] introduce their own difficulties already for the longitudinal response [25][26][27][28], We implemented our approach in a modified version of the Amsterdam density functional (ADF) code [29][30][31]. We used the augmented standard basis sets [32] provided by ADF, as these are suited for TD(C)DFT calculations.…”
Section: J Jmentioning
confidence: 99%
“…Moreover, it allows us to compare our results to static magnetizabilities reported in the literature that were obtained within the LDA. We note that exchangecorrelation vector potentials can be used within this formalism but the known functionals [24] introduce their own difficulties already for the longitudinal response [25][26][27][28], We implemented our approach in a modified version of the Amsterdam density functional (ADF) code [29][30][31]. We used the augmented standard basis sets [32] provided by ADF, as these are suited for TD(C)DFT calculations.…”
Section: J Jmentioning
confidence: 99%
“…also [6,Eq. (22.4)] and [73][74][75]) 27) where 28) and V denotes the volume of the sample. Our identification of induced electromagnetic fields with electric and magnetic polarizations is indeed consistent with this approach, because Eq.…”
Section: )mentioning
confidence: 99%
“…It has also been found that the VignaleKohn approximation in TDCDFT, even taking the lowfrequency limit, produces a finite correction, although the quantitative accuracy of such corrections has been questioned in some cases [48,49]. The work of Ref.…”
Section: Origin Of Non-local Correctionmentioning
confidence: 99%